Spirituality among Flood Victims: A Comparison between Two States - Sipon, S; Sakdan, MF; Mustaffa, CS; Marzuki, NA; Khalid, MS; Ariffin, MT; Nazli, NNNN; Abdullah, S (Elsevier Science Bv, 2024)
Indexed by WOS